Overview and safety of fingolimod hydrochloride use in patients with multiple sclerosis. (July 2014) - Ward, Melanie D; Jones, David E; Goldman, Myla D
Abstract : Introduction: Fingolimod (Gilenya®, FTY720) is an oral sphingosine-1-phosphate analogue that was approved by the FDA in 2010 for the treatment of relapsing forms of multiple sclerosis (MS). Fingolimod's mechanism of action is primarily related to lymphocyte sequestration in primary and secondary lymphoid tissues. Phase III trials demonstrated a reduction in annualized relapse rate and MRI progression in fingolimod-treated subjects compared with both placebo and IFN-β-treated subjects. Frequent adverse effects include fatigue, gastrointestinal disturbance, headache and upper respiratory tract infection. More serious, but rare, adverse events associated with fingolimod include atrioventricular block, symptomatic bradycardia, herpetic viral infections and macular edema. Areas covered: We discuss the mechanism of action, pharmacokinetics, clinical efficacy and safety profile of fingolimod in patients with relapsing MS. Expert opinion: Fingolimod is an effective treatment for relapsing MS and its oral route of administration may be preferred by some. Fingolimod is generally well tolerated but requires diligence in patient selection and monitoring. Additional information is needed regarding risk of infection, malignancy and rebound disease with long-term use of fingolimod.